Reared parasitic wasps attacking hesperiids from Western Ghats (Kerala, India) with description of a new species of Dolichogenidea (Hymenoptera: Braconidae) as a larval parasitoid of Thoressa evershedi (Evans) (Lepidoptera: Hesperiidae) - Gupta, Ankita; S, Kalesh. (Zootaxa, 2012)
Eight species of parasitic wasps were bred from various stages of five species of hesperiids viz. Thoressa evershedi (Evans), Pelopidas mathias (Fabricius), Udaspes folus (Cramer), Borbo cinnara (Wallace) and Caltoris sp. inhabiting Western Ghats, Kerala, India. One new species, Dolichogenidea kunhi Gupta & Kalesh, is described and illustrated from Kerala, India, and its relationship with closely allied species is discussed. This new species was bred from parasitized larvae of Thoressa evershedi (Evans) (Lepidoptera: Hesperiidae). Microgastrinae braconid species, Apanteles javensis Rohwer and Cotesia erionotae (Wilkinson) were bred from parasitized larvae of P. mathias and U. folus respectively. Brachymeria habui Özdikmen (Chalcididae) was recorded from pupae of U. folus. Two hyperparasitoids, Eurytoma manilensis Ashmead (Eurytomidae) & Pediobius foveolatus (Crawford) (Eulophidae) were bred from larvae of B. cinnara. Egg parasitoid, Ooencyrtus papilionis Ashmead (Encyrtidae) and pupal parasitoid Brachymeria lasus (Walker) (Chacididae) was recorded from Caltoris sp. Information on the parasitoid distribution, brief diagnosis of each species with a habitus photograph for easy identification, host association, host caterpillars, caterpillar host plants, and taxonomic comments are provided.